2022
DOI: 10.1186/s43046-022-00132-5
|View full text |Cite
|
Sign up to set email alerts
|

Her2/EGFR-PDGFR pathway aberrations associated with tamoxifen response in metastatic breast cancer patients

Abstract: Background Metastatic breast cancer (MBC) is a major health problem worldwide. Some patients improve on tamoxifen and others do not respond to treatment. Therefore, the aim of the current study is to assess genetic aberrations in the Her2/EGFR-PDGFR pathway associated with tamoxifen response in MBC patients. Methods This is a retrospective cohort study, including 157 hormone receptors positive, locally recurrent inoperable and/or MBC patients on ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…On the other hand, GAB1 has been reported to be responsible for restoring PI3K/AKT1 pathway activation in HGF-induced resistance to MET inhibitors (JNJ-38877605, PHA-665752, crizotinib) and anti-MET antibody (DN30 Fab) [ 136 ]. GAB1 is associated with tamoxifen resistance in metastatic breast cancer patients [ 137 ]. Furthermore, it has been reported that chronic lymphocytic leukemia (CLL) cells treated with ibrutinib lead to an increase in GAB1 mRNA and protein levels.…”
Section: Role Of Gab1 In Cancermentioning
confidence: 99%

The Role of GAB1 in Cancer

Pérez-Baena,
Cordero-Pérez,
Pérez-Losada
et al. 2023
Cancers
“…On the other hand, GAB1 has been reported to be responsible for restoring PI3K/AKT1 pathway activation in HGF-induced resistance to MET inhibitors (JNJ-38877605, PHA-665752, crizotinib) and anti-MET antibody (DN30 Fab) [ 136 ]. GAB1 is associated with tamoxifen resistance in metastatic breast cancer patients [ 137 ]. Furthermore, it has been reported that chronic lymphocytic leukemia (CLL) cells treated with ibrutinib lead to an increase in GAB1 mRNA and protein levels.…”
Section: Role Of Gab1 In Cancermentioning
confidence: 99%

The Role of GAB1 in Cancer

Pérez-Baena,
Cordero-Pérez,
Pérez-Losada
et al. 2023
Cancers
“…Worldwide, breast cancer (BC) has an incidence rate of 11.7% (2,261,419 new cases), just slightly greater than the prevalence of lung cancer (11.4%) [1]. Among all cancers, breast cancer is one of the most common, representing 32% of cases in the latest information available from Egypt's NCRP, the National Cancer Registry Programme [2]. Despite high survival rates in many developed nations, recent data show that Egypt's has remained dismal, especially when measured over a period of five years [3].…”
Section: Introductionmentioning
confidence: 99%